A Vinyl Radical Cyclization Route to Hydroxycyclohexene Fused Carbocycles - Chaudhuri, Shiladitya; Maity, Susama; Roy, Mahua; Ray, Paramita; Ray, Jayanta K. (Asian Journal of Chemistry, 2015)
Some hydroxycyclohexene fused carbocycles derivatives were synthesized from 6-bromo-hepta-1,5- dien-4-ol derivatives using a mediator, tri-n-butyltin hydride (TBTH) and an initiator, azobisisobutyronitrile (AIBN) in refluxing benzene.